CONSERVATION-RESTORATION AND CONSERVATION SCIENCE - THE CHALLENGE OF TRANSDISCIPLINARITY - Mechthild Noll-Minor (Ochrona Dziedzictwa Kulturowego)
Transdisciplinarity has shaped the development of both conservation science and conservation-restoration. The history of conservation science demands the commitment of all involved specialists to follow a common vision in the field. The present article highlights some key lessons to assist in closing the gap between the promotion of high-level research projects and the development and assessment of proficient professional practice in conservation science and conservation-restoration. The necessary framework conditions should also be brought to the attention of responsible politicians. Reflecting on conservation theory and practice “at the turn of the millennium” I propose to take a closer look at interdisciplinary work devoted to maintenance of Cultural Heritage since the beginning of the 20th century.